Vaginal practices, microbicides and HIV: what do we need to know? - Adriane Martin Hilber; Matthew Chersich; Janneke van de Wijgert; Helen Rees; Marleen Temmerman (2007)
The goal of a safer vaginal environment could be reached by identifying harmful vaginal practices and an effective microbicide, thereby increasing options for HIV prevention